Cultural Healing and Ageing: The Effect of Traditional Therapies on the Psychosocial Health of Older Cameroonians - Nahlela, Tasama Julliet; Mboshi, Nsagha Sarah; Maxwell, Sigala (Journal of Research in Innovative Teaching and Inclusive Learning, 2025)
This paper examines how traditional therapies influence the psychosocial well-being of older adults in Cameroon’s Grassfields, focusing on the Bali Nyonga community. Using a systematic literature review of studies published between 2000 and 2025, the analysis identifies three primary forms of cultural healing: herbal medicine, ritual practices, and psychosocial or counseling support. Evidence indicates that engagement in these therapies enhances social support networks, buffers against depressive symptoms, and contributes to improved quality of life. Elders and healers consistently describe cultural healing as vital for sustaining resilience, dignity, and community belonging in later life. However, modernization, urban migration, and religious change are eroding the intergenerational transmission of indigenous knowledge, placing elders at risk of loneliness, identity loss, and psychological distress. Despite these pressures, traditional therapies continue to provide holistic care that biomedical systems alone often fail to deliver. The study highlights the need for health and social policies that integrate indigenous practices to strengthen elder support and advance cross-cultural gerontological understanding.